PENGARUH TIME BUDGET PRESSURE DAN RISIKO AUDIT TERHADAP KUALITAS AUDIT (SURVEY PADA AUDITOR DI KANTOR AKUNTAN PUBLIK DI BANDUNG) - Suryo, Medianto (Program Studi Akuntansi FPEB UPI, 2017)
Empirically the application of principles of corporate governance can improve the quality of financial statements. However, in the implementation of Good Corporate Government and the quality of financial statements has not been done perfectly. Based on the results of research indicates that the failure of GCG implementation in Indonesia can be seen from various cases of audit failure. Based on the above, it shows that GCG mechanism is not working properly, where the stakeholders can not use the financial statements because of the low quality of financial statements or irrelevant and unreliable. This study will provide an overview of the influence of time budget pressure and audit risk on audit quality at public accounting offices in Bandung. This research uses path analysis with Time Budget Pressure variables, Audit Risk, and Audit Quality. The result of the research shows that both independent variable (Time Budget Pressure and Audit Risk) give contribution (influence) to the Quality of Audit equal to 34,20%. While the rest of 65.80% influenced by other factors outside the two independent variables.